A search for synbiotics: effects of enzymatically modified arabinoxylan and Butyrivibrio fibrisolvens on short-chain fatty acids in the cecum content and plasma of rats. Issue 4 (18th March 2016) - Nielsen, Tina S.; Jensen, Bent B.; Purup, Stig; Jackson, Stephanie; Saarinen, Markku; Lyra, Anna; Sørensen, Jens F.; Theil, Peter K.; Knudsen, Knud Erik B.
Abstract : Identification of dietary strategies to increase large intestinal production and absorption of short-chain fatty acids (SCFAs), especially butyrate, is of great interest due to the possible health promoting effects. Abstract : Identification of dietary strategies to increase large intestinal production and absorption of short-chain fatty acids (SCFAs), especially butyrate, is of great interest due to the possible health promoting effects. We explored the effect of an enzymatically modified arabinoxylan-rich diet (EAXD) versus a Western-style control diet (WSD) low in dietary fiber with or without orally administrated Butyrivibrio fibrisolvens, a butyrate producer, on the SCFA pool in the cecal content and feces and the SCFA concentration in the blood of rats. The pool of acetate, butyrate and total SCFA was more than double in the cecal content from EAXD-fed rats compared with WSD-fed rats, and this was also reflected as an increase in portal plasma SCFA concentrations. Acetate, propionate and total SCFA concentrations were higher in mixed venous plasma following the EAXD. The number of B. fibrisolvens did not increase significantly in cecal content following administration of the bacteria. Furthermore, there was no interaction between the EAXD and B. fibrisolvens on the measured parameters.